A comparative analysis of the impact of the COVID pandemic and the government restrictions on the Czech Republic and Sweden in 2020 - Sabelová, Kateřina (2021)
The goal of this thesis was to research the difference in effect of the government restrictions in response to the COVID-19 pandemic in the Czech Republic and Sweden. The Czech Republic serves as the representative country with higher level of government restrictions. The overview of restrictions in both countries was used to distinguish between the restriction levels in the two respective countries. The Difference in Difference method was used. GDP growth rate, GDP in million euro, consumption growth rate, saving rate, unemployment rate, and the index of industrial production were set as indicators of the state of the economy. The results of the regression showed a significant difference between Sweden and the Czech Republic for all the observed dependent variables except the industrial production. From the results it can be assumed that the more stringent restrictions in the Czech Republic were a cause for a larger decrease in the GDP growth rate, consumption growth rate and a larger increase in the saving rate. The unemployment rate decreased more in Sweden, possibly due to a lower level of economic help from the government.